Clem Sunter's transformational leadership discourse: a linguistic analysis - Eley, Georgina Jane (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2009)
Since the 1970s, two distinct leadership styles have been recognised in the fields of business and organisational research - transactional and transformational leadership. Transactional leadership is seen to resemble managerial-type leadership where followers fulfil their duties in return for rewards that satisfy their self-interest, such as pay or promotion. Transformational leadership, as the label suggests, is leadership that is seen to transform followers from their everyday selves to their better selves (Yukl 1998). Transformational leaders motivate followers by appealing to their higher-order needs, offering incentives for compliance such as feelings of personal empowerment, a sense of moral self-actualisation and an emphasis on the individual's contribution to the community at large (Harvey 2004). These leaders have been observed to emerge and thrive within contexts fraught with socio-political and economic turbulence, where they maximise the uncertainty of the environment to instigate change. Transformational leaders are seen to be especially adept at using discourse to foster strong, persuasive interpersonal relations with their followers. This research reports on, particularly, the interpersonal dimension of Clem Sunter's transformational discourse; he being a prominent South African scenario planner and business leader. It is essentially a qualitative study that describes Sunter's discourse in three of his texts written in 1996. The end to Apartheid in 1994 and transition from White to Black governance meant that the socio-political climate of 1996 South Africa was conducive to the rise of a transformational leader like Sunter. Although the country was, ostensibly, a democracy in 1996, much social transformation was still needed at the time Sunter produced his texts. The analysis are grounded mainly in Systemic Functional Linguistics, specifically APPRAISAL theory and, to some extent, Critical Discourse Analysis theory. However, the analyses do not follow a classic CDA analysis approach, but draw rather from more recent CDA work (cf. Fairclough 2003), such as the analysis of value assumption types within the texts. This analysis clearly demonstrates that Sunter's discourse is congruent 11 with the principal insights of transformational leadership. More than this, it is argued that these findings suggest a close link between transformational leadership and the goals of the latest social order of new capitalism, a link not made in the relevant research to date. The analysis of modes of operation of ideology in the texts (cf. Thompson 1990), also deriving from CDA, reinforces this, indicating that Sunter's transformational discourse promotes and maintains the kinds of power inequalities that underpin new capitalism. The APPRAISAL analysis of Affect choices in the text reveals a high frequency of disquiet, i.e. Sunter's discourse is seen to generate feelings of insecurity and fear. This feature, interestingly, is completely inconsistent with current transformational leadership theory, but would have been an effective motivational technique given the instability of the South African socio-political context in 1996. In addition, the APPRAISAL analysis of Judgement reveals that Sunter evokes high levels of tenacity and appeals to readers' morality, ethics and feelings of group-efficacy - all higher-order needs. The argument here too is that the socio-political context enabled Sunter to stimulate disquiet and tenacity in an effective configuration to mobilise change in his reader and promote the goals of new capitalism. The thesis concludes with a reflection on the limitations of the study and makes various recommendations for future research.
Keywords: Linguistics